FRI0353 Serum proteomics profile in systemic sclerosis patients. (15th June 2017) - Santis, M De; Generali, E; Ceribelli, A; Isailovic, N; Caprioli, M; Guidelli, GM; Selmi, C
Abstract : Background: Systemic sclerosis (SSc) is characterized in virtually all patients by anti-nuclear antibodies (ANA) with anti-centromere (ACA), anti-topoisomerase I (ant-Scl70), and anti-RNA polymerase III antibodies identifying patient subgroups. However, there are no reliable biomarkers predicting SSc susceptibility and internal organ involvement. Objectives: We aimed to identify serum protein biomarkers associated with SSc and interstitial lung disease (ILD), using a highly multiplexed proteomic technology. Methods: We analyzed serum samples of 3 patients with SSc and ILD (2 limited SSc: one ANA positive and one anti-Scl70 positive, and one diffuse SSc anti-Scl70 positive), 3 patients with SSc and no ILD (ACA positive limited SSc), and 4 healthy controls. All subjects were women and age matched. Serum proteomics profiling was performed using the SOMAscan platform (SomaLogic, Inc., Boulder, CO, USA). Statistical analysis included Student's t-test and were performed using the SomaSuite software (SomaLogic, Boulder, CO, USA). Results: Proteomic analysis identified 33 proteins which differentiate SSc from HC and 9 proteins which differentiate SSc patients with and without ILD. Compared to healthy controls, SSc cases showed an altered expression of proteins involved in extracellular matrix formation and cell-cell adhesion, angiogenesis, and lymphocyte recruitment, activation, and signaling, while an overall inhibition of neutrophil function was noted. An interferon and IL-1 signatures were also found. Patients with SSc and ILD manifested increased protein levels related to intracellular signaling and cell cycle, along with an increase of monocyte chemoattractants and ligands for the leukocyte adhesion compared to SSc without ILD. We further observed a decrease in B cell stimulating factor and IL-22 signaling in SSc with ILD. Conclusions: Serum proteomic profiles can differentiate SSc from healthy controls and SSc patients with and without ILD; moreover, our results identify biomarkers with a putative pathogenetic significance. Disclosure of Interest: None declared